2019
DOI: 10.1021/acs.analchem.8b05417
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Long-Wavelength Fluorescent Probe for Highly Selective Sensing of Carboxylesterase 1 in Living Systems

Abstract: Rational design of practical probes with excellent specificity and improved optical properties for a particular enzyme is always a big challenge. Herein, a practical and highly specific fluorescent probe for carboxylesterase 1 (CES1) was rationally designed using meso-carboxyl-BODIPY as the basic fluorophore based on the substrate preference and catalytic properties of CES1. Following molecular docking-based virtual screening combined with reaction phenotyping-based experimental screening, we found that MMB (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…The authors identified the lead compound MMB, which contains a methyl ester and dichloro‐functionalization of the BODIPY (Figure 3 e). MMB was applied for live‐cell imaging, ex vivo tissue analysis of CE1 activity (tissue slices and whole organ), and live animal imaging in zebrafish [36] . Altogether, these studies highlight the utility of searching the literature for existing substrates/inhibitors and employing molecular docking to design isoform‐selective ABS probes.…”
Section: Isoform‐selective Abs Probesmentioning
confidence: 99%
“…The authors identified the lead compound MMB, which contains a methyl ester and dichloro‐functionalization of the BODIPY (Figure 3 e). MMB was applied for live‐cell imaging, ex vivo tissue analysis of CE1 activity (tissue slices and whole organ), and live animal imaging in zebrafish [36] . Altogether, these studies highlight the utility of searching the literature for existing substrates/inhibitors and employing molecular docking to design isoform‐selective ABS probes.…”
Section: Isoform‐selective Abs Probesmentioning
confidence: 99%
“…Cui et al. developed a long‐wavelength fluorescent probe 12 which can sensitively monitor carboxylesterase 1 (CES1) utilizing meso‐carboxyl‐BODIPY as the fluorophore (Figure b) . BODIPY derivatives have excellent photostabilities, and can modulate photophysical properties easily with proper substitution .…”
Section: Classification and Functions Of Cessmentioning
confidence: 99%
“…Recently, much work has integrated biological functions into biosensing to achieve biomedical functions with high sensitivity and specificity. [90][91][92] This requires that the materials used in biosensing can interact with and respond to target signals uniquely. Nucleic acid biopolymers show recognition ability to target molecules with good selectivity.…”
Section: Application In Biosensingmentioning
confidence: 99%